2018
DOI: 10.1167/18.5.4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spatiotemporal displacement on the integration of shape information

Abstract: Within a natural scene it is not uncommon for an object's shape to be revealed over time. We investigated whether the same integration of shape information that happens around a fully visible contour also happens when that information is distributed over time. In a two-interval forced-choice task, observers discriminated between a radial frequency (RF) pattern and a circle that were revealed either using an implicit slit or traced out by a dot's motion; and a line and a modulated line that were either contour-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Global shape processing, in our case based on the integration of local information around the shape's contour, can aid in the detection and discrimination of different shapes. This has been examined by numerous previous studies using radial frequency (RF) patterns (Almeida, Dickinson, Maybery, Badcock, & Badcock, 2013;Almeida, Dickinson, Maybery, Badcock, & Badcock, 2014;Baldwin et al, 2016;Bell, Badcock, Wilson, & Wilkinson, 2007;Bell, Dickinson, & Badcock, 2008;Dickinson, Han, Bell, & Badcock, 2010;Green, Dickinson, & Badcock, 2018a, 2018bLoffler, Wilson, & Wilkinson, 2003;Schmidtmann, Kennedy, Orbach, & Loffler, 2012;Wilkinson, Wilson, & Habak, 1998;Wilson & Propp, 2015). RF patterns are derived from circles by sinusoidally modulating their radius as a function of the polar angle.…”
Section: Introductionmentioning
confidence: 99%
“…Global shape processing, in our case based on the integration of local information around the shape's contour, can aid in the detection and discrimination of different shapes. This has been examined by numerous previous studies using radial frequency (RF) patterns (Almeida, Dickinson, Maybery, Badcock, & Badcock, 2013;Almeida, Dickinson, Maybery, Badcock, & Badcock, 2014;Baldwin et al, 2016;Bell, Badcock, Wilson, & Wilkinson, 2007;Bell, Dickinson, & Badcock, 2008;Dickinson, Han, Bell, & Badcock, 2010;Green, Dickinson, & Badcock, 2018a, 2018bLoffler, Wilson, & Wilkinson, 2003;Schmidtmann, Kennedy, Orbach, & Loffler, 2012;Wilkinson, Wilson, & Habak, 1998;Wilson & Propp, 2015). RF patterns are derived from circles by sinusoidally modulating their radius as a function of the polar angle.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies that examined the effect of spatial uncertainty on shape discrimination thresholds, Green and colleagues (2017Green and colleagues ( , 2018aGreen and colleagues ( , 2018bGreen and colleagues ( , 2018c found that sensitivity to curvature differences between two shapes was greatest when the phase (i.e., angular position) of the shapes varied from trial to trial. This finding suggests that spatial uncertainty affects sensitivity to contour curvature (Green et al, 2017(Green et al, , 2018a(Green et al, , 2018b(Green et al, , 2018c), but does not reveal how spatial uncertainty affects sensitivity to curvature. Baldwin et al (2016) examined the effect of spatial uncertainty on curvature detection thresholds as a function of the number of modulated cycles appearing along the contour of a shape.…”
Section: Introductionmentioning
confidence: 84%
“…More importantly, the method used here generates a combination of many RF patterns, whereas most previous studies used either single component RF patterns (e.g. Bell & Badcock, 2008Bell et al, 2007;Green, Dickinson, & Badcock, 2017, 2018a, Green, Dickinson, & Badcock, 2018bHess, Achtman, & Wang, 2001;Jeffrey et al, 2002;Schmidtmann et al, 2012;Loffler et al, 2003), combinations of two Bell et al, 2007;Lawrence et al, 2016) or three RF components (Schmidtmann, Jennings, & Kingdom, 2015). Given that the aim of this study was to explore the limits of what can be represented by compound RF patterns, the stimuli used here are combinations of an arbitrary number of RF patterns (see Methods).…”
Section: Discussionmentioning
confidence: 99%